Xylooligosaccharide Modulates Gut Microbiota and Alleviates Colonic Inflammation Caused by High Fat Diet Induced Obesity - Fei, Yanquan; Wang, Yan; Pang, Yilin; Wang, Wenyan; Zhu, Dan; Xie, Meigui; Lan, Shile; Wang, Zheng (Frontiers in Physiology, 2020)
Accumulating studies have shown that obesity leads to colonic inflammation and may increase the risk of colorectal cancer. Xylooligosaccharide (XOS) has strong antioxidant capacity and excellent antibacterial activity which could be utilized by gut microbes to maintain the ecological balance of the intestinal tract. In the present study, we explored how XOS regulate inflammation caused by high-fat diets through microbes. the changes in body weight and visceral coefficient in rats were detected , the expression levels of inflammatory factors in plasma and colon tissues were determined with ELISA and real-time quantitative PCR., the composition of microorganisms in feces, and the content of SCFA were also detected and assayed with 16Sr DNA and GC-MS. The results showed that the weight gain trend of the high-fat group treated by XOS (HFD+XOS) was significantly lowered down, plasma levels of monocyte chemoattractant protein-1 (MCP-1), tumor necrosis factor (TNF-α) and lipopolysaccharide (LPS) were significantly reduced. The expression of TNF-α mRNA in colon tissue decreased significantly, while the expression of tight junction protein Occludin (Ocln) gene increased significantly. The microbial abundance in the feces decreased, while the proportion of Bacteroidetes/Firmicutes increased, and the number of beneficial bacteria increased as dominant microbes. Accordingly, the abundance of of producing-SCFA bacterium and the content of SCFA greatly increased in the gut of the HFD+XOS group. A correlation between the abundance of these bacteria such as Prevotella, Bacteroidetes and Lactobacillus and SCFA content was found in the correlation analysis. Therefore, we believe that XOS can regulate gut microbial composition to promote the increase of SCFA content in the gut, thus alleviating colonic inflammation.